2010
DOI: 10.1111/j.1523-1739.2009.01422.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Land Facets to Plan for Climate Change: Conserving the Arenas, Not the Actors

Abstract: Even under the most optimistic scenarios, during the next century human-caused climate change will threaten many wild populations and species. The most useful conservation response is to enlarge and link protected areas to support range shifts by plants and animals. To prioritize land for reserves and linkages, some scientists attempt to chain together four highly uncertain models (emission scenarios, global air-ocean circulation, regional circulation, and biotic response). This approach has high risk of error… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
203
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(209 citation statements)
references
References 67 publications
3
203
0
Order By: Relevance
“…Researchers are highlighting the importance of identifying and protecting landscape-scale features such as topographic and climatic heterogeneity, elevation gradients, solar insolation, soil types, geology, and riparian corridors to aid species' adaptation to climate change (Peterson 2003, Seavy et al 2009, Ackerly et al 2010, Anderson and Ferree 2010, Beier and Brost 2010, Dobrowski 2011. Our method combines this information with climate change stress and potential constraints to adaptation to provide a map of climate adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers are highlighting the importance of identifying and protecting landscape-scale features such as topographic and climatic heterogeneity, elevation gradients, solar insolation, soil types, geology, and riparian corridors to aid species' adaptation to climate change (Peterson 2003, Seavy et al 2009, Ackerly et al 2010, Anderson and Ferree 2010, Beier and Brost 2010, Dobrowski 2011. Our method combines this information with climate change stress and potential constraints to adaptation to provide a map of climate adaptation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that diverse environmental factors, such as temperature, precipitation, soil, elevation, and slope, influence the ecological process and contribute to the formation of biodiversity patterns [21,[59][60][61]. In particular, topography could be a significant variable in predicting the migration of species which is attributable to long-term effects, such as climate change [11,23]. However, we argue that care needs to be taken regarding the topographic classification approach to be used when topographic characteristics are considered as a surrogate of species.…”
Section: Topographic Classes As a Surrogate Of Speciesmentioning
confidence: 99%
“…For instance, Brost and Beier [19] found that topographic linkages drawn by the LCM can include the path of focal species. However, these studies mainly considered topographic variables related to the topographic form, such as elevation, slope angle, and insolation, to design linkages, and did not reflect the flow of energy and materials [11,23].…”
Section: Designing Topographic Linkages To Accommodate Climate Changementioning
confidence: 99%
“…For example, short-term resiliency of a site may be a function of the amount and accessibility of similar environments in the neighborhood of the focal cell, since having 545 larger and more connected local populations should facilitate population recovery of the constituent organisms (and thus ecosystem functions) following disturbance-which is the premise of our two resiliency metrics. However, long-term resiliency of a site may also be a function of the amount and accessibility of diverse environments in the neighborhood of the focal cell, since having a diverse assemblage of environments nearby increases the opportunities 550 for different organisms to fill the ecological niche space as the environment (e.g., climate) changes over time-which is the premise of the metrics used in the geophysical stage approach proposed by others (e.g., Anderson and Ferree 2010;Beier and Brost 2010;Beier 2012;Beier et al 2015). Consequently, while still unclear, it is possible that the factors driving short-term resiliency may differ from those driving long-term resiliency in the face of environmental 555 change.…”
Section: Second While Our Approach Relies On Objective Measures Of Imentioning
confidence: 99%
“…One approach has been to focus solely on the 65 geophysical environment without attention to the biota, and identify and prioritize representative, diverse and connected geophysical settings based on one or more metrics (e.g., Anderson et al 2014;Beier et al 2015). Here the goal is to conserve the abiotic stage and allow the biota to change and "play out" on this stage over time, especially in response to climate change (Beier and Brost 2010;Beier 2012). For example, Anderson et al (2014) measured site resiliency using 70 a combination of two metrics: 1) landscape diversity, which refers to the number of microhabitats and climatic gradients available within a given area based on the variety of landforms, elevation range, soil diversity, and wetland extent and density, and 2) local connectedness, which refers to the accessibility of neighboring natural areas.…”
Section: Introductionmentioning
confidence: 99%